ENVIRONMENTAL EXPENDITURES OF IRON-PROCESSING ENTERPRISES OF KRYVYI RIH - Кошарна, С. (Київський національний університет імені Тараса Шевченка, 2018)
The development of industry and the consequences of the development have a negative effect on the environment, so legislative authorities are enforced to move from discussion of environmental problems to their actual solving. Accordingly, it is required to render more attention to, and provide monitoring of, industrial enterprises (specifically metallurgical ones, which are the largest environmental contaminants in Ukraine). Part of the financial resources of these enterprises must be allotted not only to meet the requirements presented in Section 3 of the Tax Code of Ukraine, which regulates taxes for environmental protection, but also to pay other reasonable environment-oriented expenditures. The subjects of the study are the data on the theoretical basis and study methods concerning environment-oriented expenditures, economic and organizational decisions chosen as the study objective one of the above-mentioned enterprises – ArcelorMittal Kryvyi Rih, and the geochemical characteristics of the environment in the areas near the enterprises. The offer of the new scheme of classification of environment-oriented expenditures on the base of existent classifications proposed by Savchenko O.F., Saienko K.S., and Tuiakova Z.S., and an offer of increasing of investments in the environmental education of the Kryvyi Rih region population in order to raise the level of environmental responsibility are presented in the paper. This paper contains the results of the comparative analysis of amounts and patterns of environment-oriented expenditures of the largest ore mining and metallurgical enterprises in the areas of their activities.

Розвиток промисловості та його наслідки негативно впливають на навколишнє середовище, що змушує законодавчі органи переходити від дискусійного періоду з обговорення екологічних питань до їх фактичного вирішення. Відповідно, все більшої уваги та контролю нині вимагають промислові підприємства (зокрема металургійні, як одні з найбільших забруднювачів НС України), частина фінансових потоків яких мусить бути направлена не лише на задоволення вимог третього розділу Податкового кодексу України, що регламентує особливості екологічних податків, але й на ряд інших екологічних витрат, кожна з яких має вагомі підстави. Предметом дослідження є теоретико-методологічні дані щодо екологічних витрат, економіко-організаційні рішення, обраного за об'єкт дослідження, металургійного підприємства з вироблення та переробки залізної руди – ПАТ "АрселорМіттал Кривий Ріг" та геохімічний стан середовища у безпосередній близькості до нього й інших промислових об'єктів. Сформульовано пропозиції щодо нового угруповання екологічних витрат, утвореного на основі вже існуючих класифікацій О.Ф. Савченко, К.С. Саєнко та З.С. Туякової, а також щодо збільшення відсотка інвестування в екологічну освіту населення Кривого Рогу з метою підвищення рівня екологічної відповідальності. Проведено зіставлення обсягів і структури екологічних витрат добувних підприємств у межах найбільших залізорудних і металургійних регіонів.
ЕКОЛОГІЧНІ ВИТРАТИ ЗАЛІЗОПЕРЕРОБНИХ ПІДПРИЄМСТВ КРИВОГО РОГУ
Keywords: environment-oriented expenditures; regulatory documents; classification of environment-oriented expenditures; investment project; geochemical analysis; екологічні витрати; нормативно-законодавчі акти; угруповання екологічних витрат; інвестиційні проекти; геохімічний аналіз